Germany : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
The three-point VAT increase is part of a package in which unemployment payroll taxes will be reduced. Risks to the recovery are balanced but the range of forecasts for 2007 is unusually wide. The priority for Germany is to transmit its external strength to the domestic economy, thus further broadening the recovery and creating conditions for sustained high growth. The authorities are undertaking a review of active labor market policies (ALMPs) with a view to curtailing their number.